Histocompatibility antigens, autoantibodies, and immunoglobulins in alcoholic liver disease. Issue 6038 (25th September 1976) - Bailey, R J; Krasner, N; Eddleston, A L; Williams, R; Tee, D E; Doniach, D; Kennedy, L A; Batchelor, J R
Abstract : Determination of histocompatibility antigens in 63 patients with alcoholic liver disease showed that HLA-B8 was more prevalent in patients with cirrhosis than in controls, but among those with fatty liver and minimal fibrosis the prevalence of this antigen was normal. Another noticeable difference was the absence of HLAA28 in the cirrhotic group. In the total series of 219 patients the prevalence of antinuclear and smooth muscle antibodies was raised; they were especially prevalent in patients with cirrhosis. Raised serum IgA and IgG concentrations were also common (found in 50% and 37% respectively) and were again significantly associated with cirrhosis. In contrast, serum IgM levels, which were raised in 46% of cases, were not significantly related to the presence of cirrhosis but correlated significantly with the degree of portacaval shunting. These results support recent evidence suggesting that immune responses may be implicated in alcohol-induced liver damage, particularly in its progression to cirrhosis.